Avaliação do nível de atividade física e a percepção da qualidade de vida dos escolares do ensino fundamental - Reis, Giselle Capistano (Universidade Federal do Tocantins, 2019)
The objective of this study was to evaluate the level of physical activity and perception of the quality of life of schoolchildren in a school in the municipality of Miracema TO. It is known that the practice of physical activity has been associated with health benefits, however, children do not always perform enough physical activity in their daily life, which can make them young and sedentary adults. Sedentary lifestyle is one of the most important modifiable risk factors for health promotion, together with the perception of quality of life. This result allows us to understand beyond physical practice the feelings and perceptions that children have in the school environment. For the evaluation, we used instruments of the Physical Activity Level (NAF) and the perception of Quality of Life (QL), validated in Brazil. The research was carried out with 13 children (7 boys and 6 girls) with ages ranging from 10 to 12 years of age. Data analysis showed that in the face of various problems that the school unit is in, the children present a positive Physical Activity Level, classified as very active, being fundamental the figure of the physical education teacher in their classes to encourage healthy habits and structure family being a complement to well-being and active behavior, thus positively arousing in the level of physical activity and perception of the quality of life of elementary school students.